Climate responsive architecture : a design handbook for energy efficient buildings - Krishan, Arvind (New Delhi ; New York : Tata McGraw-Hill Pub. Co., 2001)
Papers presented at an international workshop held in 1995.
Includes bibliographical references.
Keywords: Dwellings -- Energy conservation -- Congresses